Civil service reform, self‐selection, and bureaucratic performance. (10th February 2020) - Gibbs, Daniel
Abstract: I use a formal model to analyze the effect of civil service protections on bureaucratic performance. In a two‐period model, a public manager observes a bureaucrat's actions for a period and decides whether to retain or attempt to remove the bureaucrat. Bureaucrats vary in terms of their intrinsic motivation and choose between careers in government or the private sector. I show that bureaucratic performance is greater in any separating equilibrium in which motivated bureaucrats choose government than in all equilibria in which they do not. Stronger civil service protections reduce the amount of effort that motivated bureaucrats must exert to distinguish themselves from their unmotivated peers in order to ensure retention. This strengthens incentives for motivated bureaucrats to choose careers in government. Stronger civil service protections, however, also reduce the ability of public managers to remove unmotivated bureaucrats. These competing effects yield a non‐monotonic and discontinuous relationship between civil service protections and bureaucratic performance. I use the model to analyze recent reforms to U.S. state and federal personnel management that have significantly rolled back traditional job protections.